The GENDER RELATIONS AND INTRA-HOUSEHOLD RESOURCE ALLOCATIONS: WOMEN’ S ACCESS TO AGRICULTURE EXTENSION AND ADVISORY SERVICES IN KABLE DISTRICT, UGANDA - Mbabazi, Peace (Advances in Social Sciences Research Journal, 2020)
Abstract Gender relations embody and justify unequal power relations in intra-household allocation and livelihood improvement strategies. While women are the main actors in agriculture production in the Kabale’s dominant smallholder farmer households, they are restricted from control and use of the production resources necessary to access Agriculture Extension and Advisory Services. Household and higher level institutional structures are within patriarchal power setting and women have to bargain through explicit and implicit ways to access household resources, each with implications on accessibility to support services needed to improve livelihood. There are however, some few cases of mutual cooperation with positive ramifications on access to extension services as well as on household livelihood outcomes. While this paper recognizes eminent reforms during the era of agriculture modernisation, these have not yet fully achieved power and institutional transformation for the meaningful positioning of women with regard to control and use of resources needed to access extension services at household level.